A Case of Aripiprazole-Induced Tardive Dyskinesia with Dramatic Evolution. (12th October 2016) - Heitzmann, Edwige; Javelot, Hervé; Weiner, Luisa; Michel, Bruno
Abstract : Aripiprazole is reported to be a good clinical safety profile antipsychotic. However, recent data suggest that the risk of tardive dyskinesia could be higher than initially thought. We report the case of aripiprazole-induced tardive dyskinesia with dramatic evolution in a patient with several risk factors, including older age and exposure to antipsychotic over a period longer than six months. This case and its dramatic evolution, associated with other cases recently published, suggest reconsidering the real risk of tardive dyskinesia associated with aripiprazole, particularly in the elderly.